2015
DOI: 10.3390/v7092858
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Nuclear Architecture and Epigenetic Signatures during African Swine Fever Virus Infection

Abstract: Viral interactions with host nucleus have been thoroughly studied, clarifying molecular mechanisms and providing new antiviral targets. Considering that African swine fever virus (ASFV) intranuclear phase of infection is poorly understood, viral interplay with subnuclear domains and chromatin architecture were addressed. Nuclear speckles, Cajal bodies, and promyelocytic leukaemia nuclear bodies (PML-NBs) were evaluated by immunofluorescence microscopy and Western blot. Further, efficient PML protein knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 76 publications
(104 reference statements)
1
29
0
1
Order By: Relevance
“…The recruitment of pA104R to viral DNA replication sites (cytoplasmic factories) corroborates the results obtained with ASFVinfected macrophages (8) and strengthens the idea that the viral protein may participate in ASFV genome packaging. In parallel, its nuclear localization reinforces the concept that pA104R may also participate in the viral DNA replication that occurs inside this cellular compartment (46) and/or in the heterochromatization of the cell genome (47). The latter phenomenon could facilitate viral infection by silencing genes required to mount an immune response.…”
Section: Figsupporting
confidence: 69%
“…The recruitment of pA104R to viral DNA replication sites (cytoplasmic factories) corroborates the results obtained with ASFVinfected macrophages (8) and strengthens the idea that the viral protein may participate in ASFV genome packaging. In parallel, its nuclear localization reinforces the concept that pA104R may also participate in the viral DNA replication that occurs inside this cellular compartment (46) and/or in the heterochromatization of the cell genome (47). The latter phenomenon could facilitate viral infection by silencing genes required to mount an immune response.…”
Section: Figsupporting
confidence: 69%
“…The late transcription of A104R gene is corroborated by pA104R expression from 12 hpi onward, but not in the presence of Arabinose AraC, a strong transcription inhibitor. The recruitment of pA104R to viral factories strengthens the idea that this viral protein may participate in ASFV genome packaging [71], whereas, its nuclear localization suggests that pA104R may also participate in the viral DNA replication and/or in the heterochromatization of the cell genome [81], thus facilitating the viral infection—although this is not its main function. Finally, the A104R downregulation by siRNA (−27% at 16 hpi) has been proven to affect the production of infectious progeny given by a reduction in the viral yields (−82.0%), less viral genome copy number (−78.3%), and late viral transcription repression (B646; −47.6%) still, without interfering with the transcription of the early viral gene CP204L [71].…”
Section: A104r—histone-like Proteinmentioning
confidence: 85%
“…Recent studies have shown that some viruses subvert cellular epigenetic mechanisms and recruits host transcription factors to their advantage and modulate chromatin structure ensuring its successful existence in the host[16]. In order to identify the role of TLR4 affecting transcription of the chromatin template, global alterations of histone modifications was observed in HepG2.2.15 cells after triggering the TLR4 pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Further, there are strong evidences of interplay of viral encoded proteins in host chromatin modulation[16]. Several viruses on host cell entry elicit an epigenetic reprogramming of the host chromatin by changing methylation and acetylation status and subverting chromatin-associated enzymes which leads to a change in host chromatin structure and gene expression[22].…”
Section: Discussionmentioning
confidence: 99%